2014
DOI: 10.1002/ijc.29380
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine regulation of glioma cells invasion by astrocytes is mediated by glial‐derived neurotrophic factor

Abstract: It was suggested that the brain microenvironment plays a role in glioma progression. Here we investigate the mechanism by which astrocytes which are abundant in glioma tumors, promote cancer cell invasion. In this study, we evaluated the effects of astrocytes on glioma biology both in vitro and in vivo and determined the downstream paracrine effect of glial-derived neurotrophic factor (GDNF) on tumor invasion. Astrocytes-conditioned media (ACM) significantly increased human and murine glioma cells migration co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Our results confirmed the findings in previous studies showing that high GDNF expression promotes malignant glioma cell proliferation and migration [11, 14, 15, 21]. However, the molecular mechanisms underlying these observations remain unclear.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results confirmed the findings in previous studies showing that high GDNF expression promotes malignant glioma cell proliferation and migration [11, 14, 15, 21]. However, the molecular mechanisms underlying these observations remain unclear.…”
Section: Discussionsupporting
confidence: 82%
“…Among these, MAPK, Wnt, and mammalian target of rapamycin (mTOR) signaling pathways are closely related to glioma occurrence and development [49]. These signaling cascades primarily down-regulate tumor-suppressor genes and up-regulate tumor-causing genes in glioma [11, 15, 50-52]. Taking tuberous sclerosis complex-1 (TSC1) as an example, it acts as a tumor suppressor in complex with TSC2 to influence cell adhesion, migration, and fate determination in the central nervous system [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few experimental studies have analyzed functional roles of astrocytes in GBM biology. These studies have predominantly focused on roles of astrocytes in GBM invasion (Chen et al, ; Le et al, ; Shabtay‐Orbach, Amit, Binenbaum, Na'ara, & Gil, ; Sin et al, ). Other studies have demonstrated interactions between astrocytes and GBM cells affecting drug‐sensitivity of GBM cells, or their response to hypoxia (Chen et al, ; Jin et al, ; Lin, Liu, Ling, & Xu, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically they have been linked to the growth of neuroblastoma (Komminoth et al 1996), breast cancer (Banerjee et al 2012; Ding et al 2014), small cell lung cancer (Rudin et al 2014), thyroid cancer (Hong et al 2008; Wells and Santoro 2009), pancreatic cancer (Donahue and Hines 2009) and testicular cancer (Sariola and Meng 2003). GDNF promotes perineural invasion and metastasis of brain tumor (Ilhan-Mutlu et al 2013), head and neck squamous cell carcinoma (Roh et al 2015), glioma (Shabtay-Orbach et al 2014), pancreatic cancer (He et al 2014; Wang et al 2014b) and colon cancer (Huang et al 2014). GDNF family members also increase resistance to the chemotherapy in the prostate (Huber et al 2015) and breast cancer (Ding et al 2014; Morandi et al 2013), while reduction of GDNF level decreased metastasis of mammary gland cancer and related pain in the bone of rat (Meng et al 2015).…”
Section: Gdnf Familymentioning
confidence: 99%